Causes and remedies for Japan's long-lasting recession: Lessons for the People's Republic of China - Naoyuki Yoshino; Farhad Taghizadeh-Hesary (Asian Development Bank Institute (ADBI), 2015)
Japan has suffered from sluggish economic growth and recession since the early 1990s. In this paper, we analyze the causes of the prolonged slowdown of the Japanese economy (the lost decade). Economics Nobel laureate Paul Krugman has argued that Japan's lost decade is an example of a liquidity trap. However, our empirical analysis shows that stagnation of the Japanese economy comes from its vertical IS curve rather than a horizontal LM curve, so the Japanese economy faces structural problems rather than a temporary downturn. The structural problems mainly come from the aging demographic, which is often neglected in other studies, and also from the allocation of transfers from the central government to local governments, and the unwillingness of Japanese banks to lend money to startup businesses and SMEs, mainly because of Basel capital requirements. Many countries, like the People's Republic of China, are expected to face similar issues, particularly the aging population, and so are very much concerned about the long-term recession that Japan has experienced. This paper will address why the Japanese economy has been trapped in a prolonged slowdown and will provide some remedies for revitalizing the economy.
Keywords: E12; E62; 330; Japan's lost decade; recessions; prolonged slowdown